Triticum durum productivity and adaptability of two genotypes under water deficit in Algerian high plains - Belguendouz, Amina; Sahnoune, Mohamed (Future Science, 2024)
Over the past few decades, Algeria has experienced a significant decline in rainfall patterns, which has been exacerbated by increasing hot spells leading to elevated rates of evapotranspiration. This combination of factors has induced severe water stress, critically impacting agricultural productivity, particularly in cereal production. Recognizing the urgency of this issue, our study was conducted over two consecutive cropping seasons at the experimental agricultural site of Ibn Khaldoun University in Tiaret, located in the western region of Algeria. We specifically investigated the performance of two durum wheat cultivars, ACSAD 297 and CTA 159, under conditions of water stress typical of the Algerian high plains. Our research focused on the impacts of water deficits during the grain filling phase, assessing their effects on seed formation, seed quality, and overall yield development. The results highlighted that contributions from various plant components to grain filling were notably affected by water availability, with lower leaves contributing 22%, the flag leaf 15%, the ear 14%, the ear neck 10%, and awns less than 1%. Notably, the ACSAD 297 cultivar exhibited superior drought tolerance compared to CTA 159, indicating its potential for cultivation in arid conditions. Furthermore, we established strong correlations between grain diameter, thousand grain weight, and stem height, which could inform future breeding initiatives. These findings not only provide important targets for enhancing drought resistance in durum wheat but also have broader implications for improving wheat productivity in semi-arid regions around the world, contributing to food security in the face of climate change.